2002
DOI: 10.1046/j.1365-2249.2002.01852.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fusobacterium nucleatum on the T and B cell responses to Porphyromonas gingivalis in a mouse model

Abstract: Periodontal disease results from the inflammatory response to bacteria in dental plaque (reviewed in [1]). Although there are well over 300 different bacterial species in the plaque, progression to periodontitis depends not on bacterial load, but on the presence of specific periodontopathic bacteria. The major pathogens identified at the 1996 World Workshop in Periodontics as causative agents are Porphyromonas gingivalis, Actinobacillus actinomycetemcomitans and Bacteroides forsythus [2]. P. gingivalis has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 36 publications
1
41
0
2
Order By: Relevance
“…The data suggest that F. nucleatum modulates the antibody response of the host to T. forsythia. A similar outcome was reported in a previous study in which a decreased antibody response to P. gingivalis was observed in mice previously immunized with F. nucleatum (15). The low IgG titers to T. forsythia and F. nucleatum in the sham-infected mice (Fig.…”
Section: T Forsythia and F Nucleatum Mixed Challenge Cooperatively supporting
confidence: 90%
See 2 more Smart Citations
“…The data suggest that F. nucleatum modulates the antibody response of the host to T. forsythia. A similar outcome was reported in a previous study in which a decreased antibody response to P. gingivalis was observed in mice previously immunized with F. nucleatum (15). The low IgG titers to T. forsythia and F. nucleatum in the sham-infected mice (Fig.…”
Section: T Forsythia and F Nucleatum Mixed Challenge Cooperatively supporting
confidence: 90%
“…Strikingly, F. nucleatum coinfection led to a dampening of the antibody response to T. forsythia. Although we do not know the reason for this phenomenon, a previous study also observed a dampened antibody response to P. gingivalis following exposure to F. nucleatum (15). It is also likely that F. nucleatum suppresses the expression or the availability of antigenically dominant T. forsythia antigens, a result which causes a reduced bacterium-specific antibody response.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The gamma-irradiation may be an excellent alternative to UV for large-scale bacterial inactivation, since it can penetrate into the deeper layer of bacterial culture [27]. It has been documented that immunization with F. nucleatum did not induce the production of cross-reactive antibodies to other oral micro-organisms [28]. Our results showed that anti- S. mutans serum did not cross-react with F. nucleatum (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…Serum levels of antibodies to hHSP60, P. gingivalis GroEL and P. gingivalis whole cells were determined using an ELISA technique. 18 Each of the antigens (recombinant hHSP60 (2 lg ⁄ ml), P. gingivalis GroEL (2 lg ⁄ ml), and P. gingivalis ATCC 3277 (1 lg ⁄ ml)) was coated onto 96-well high-binding plates (Maxisorb Immunoplates, Nunc, Roskilde, Denmark). Diluted (1:100) serum samples were added followed by peroxidase-conjugated rabbit anti-human IgG (DAKO, Glostrup, Denmark).…”
Section: Methodsmentioning
confidence: 99%